Cell‐free expression of recombinant antigens of Borrelia burgdorferi and microarray‐based multiplex detection using different patient sera. Issue 4 (12th March 2014) - Richter, Carolin; Konstantinidis, Kosta; Asen, Iris; Kneusel, Richard; Hubbuch, Jürgen
<x xml:space="preserve">Abstract</x> Lyme borreliosis is the most common tick‐borne disease in North America and Europe. A two‐test approach (an ELISA followed by immunoblots) for testing current and past infection has been adopted in most countries. However, the heterogeneity of Borrelia antigens (ags) and the semiquantitative character of the immunoblot remain a limitation. By combining a microarray system with cell‐free expression, we established a procedure for the expression and subsequent printing of different Borrelia ags onto several multiwell microarray plate surfaces. We successfully expressed and partially purified 11 immunodominant ags of Lyme borreliosis from different Borrelia species in a self‐generated Escherichia coli cell‐free system. Using sera from patients suffering from Lyme disease and different specific mAbs, proteins could be reproducibly detected on the microarray plates. To confirm the diagnostic outcome of the new assay, a comparison to the same cell‐based expressed, purified, and printed Borrelia ags was performed. In summary, this approach serves as a proof of principle for the identification of potential biomarkers and offers the possibility of multiplex protein detection for specific diseases.